1981
DOI: 10.1016/0304-4165(81)90068-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of the C-terminal octapeptide of cholecystokinin and of a cholera toxin pretreatment on the kinetics of rat pancreatic adenylate cyclase activity

Abstract: (1) The kinetic parameters of rat pancreatic adenylate cyclase were evaluated, using GTP, p[NH]ppG or GTP gamma S as nucleotide activator, cholecystokinin as peptide hormone, and GDP beta S and dibutyryl cyclic GMP as inhibitors of guanosine triphosphate and CCK-8, respectively. The time courses of activation and the degree of activation at steady state (EA/ETOT) were compatible with a simple two-state model of activation-deactivation based on a pseudo-monomolecular activation process (rate constant kappa+1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…In [4] we used the whole erythrocyte cytosol and cholera toxin to activate adenylate cyclase in pancreatic plasma membranes. Using similar conditions with [c~-32P] NAD +, we observed that cytosolic proteins were labelled in addition to plasma membrane proteins (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In [4] we used the whole erythrocyte cytosol and cholera toxin to activate adenylate cyclase in pancreatic plasma membranes. Using similar conditions with [c~-32P] NAD +, we observed that cytosolic proteins were labelled in addition to plasma membrane proteins (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…One volume of this membrane suspension was added to an equal volume of the complete cytosol of packed human erythrocytes [4] or of a 'cytosolic factor' (purified as in [18]) and to 3 vol. reaction medium so as to obtain, at final concentration, 25/~M [a.32p].…”
Section: Adp-ribosylationmentioning
confidence: 99%
See 3 more Smart Citations